2019
DOI: 10.1136/postgradmedj-2018-136135
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in medical doctors: a systematic review

Abstract: IntroductionResilience can be difficult to conceptualise and little is known about resilience in medical doctors.AimsThis systematic review discusses the existing literature on influences on resilience levels of medical doctors.MethodsThe bibliographic databases PubMed, MEDLINE, EMBASE and PsycINFO were searched from 2008 to November 2018 using keyword search terms resilience* AND (“medical physician*” OR doctor* OR surgeon* OR medical trainee* or clinician*).ResultsTwenty-four studies were deemed eligible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
57
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 45 publications
6
57
1
1
Order By: Relevance
“…Importantly, our research has identified that the trainees who participated already recognised and actively used a number of approaches for addressing challenges and for maintaining their own well-being. However, it also adds weight to the argument that maintaining well-being is not something for which the responsibility rests with individuals alone 30. Our participants repeatedly highlighted the importance of their workplaces and their colleagues for maintaining their well-being.…”
Section: Discussionmentioning
confidence: 75%
“…Importantly, our research has identified that the trainees who participated already recognised and actively used a number of approaches for addressing challenges and for maintaining their own well-being. However, it also adds weight to the argument that maintaining well-being is not something for which the responsibility rests with individuals alone 30. Our participants repeatedly highlighted the importance of their workplaces and their colleagues for maintaining their well-being.…”
Section: Discussionmentioning
confidence: 75%
“…This factor might explain another of our findings, which related older age with decreased resilience, as opposed to other studies that reported the inverse relationship. 10 , 12 In addition, recent research suggests that professionals working on the front lines during the COVID-19 pandemic experienced a lower prevalence of burnout than their colleagues, 23 suggesting an interesting line of future research. Nonetheless, work shift and its relationship with resilience have rarely been reviewed in the literature, and no relationship has been established 6 ; given the demonstrated role of work shift as a predictor of resilience, this relationship should be analyzed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies show a correlation between having a partner 10 and children 11 and better levels of resilience in nursing professionals, and indicate that age, colleagues' support, and work autonomy increase resilience in doctors. 9,12 However, the working conditions of nurses are also determinants of the development of resilience, which has been shown to be decreased when nurses suffer stress and workplace bullying. 13,14 Despite the numerous studies on resilience in health professionals 6,10 and the need to implement strategies to improve the situation of emergency workers, 15,16 institutions still do not take active measures to strengthen resilience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning healthcare workers, McKinley et al [37] suggest that resilience may be difficult to conceptualize and that resilience levels in doctors are influenced by demographics, personality, organizational or environmental factors, social support, leisure, having overcome previous adversity and having undergone interventions to improve resilience [4]. Many studies agree in highlighting how resilience is a protective factor against the development of secondary traumatic stress and burnout among human service professionals [38] and in nurses [39][40][41].…”
Section: Resilience and Hardiness As Protection Factors In Healthcarementioning
confidence: 99%